PENINGKATAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR SISWA KELAS IV MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN METODE PERMAINAN OPEN THE BOX - Agil Setiawan; Hadiyanti, Agnes Herlina Dwi; Kriswanto, Yohanes Bruri (Jurnal Pendidikan Dasar, 2022)
This research aims to improve students social skills and students learning outcomes of class IV Kanisius Demangan Baru I Elementary School in social learning through a problem based learning model. This type of research used is Classroom Action Research . The research subjects were 23. This research was conducted in the even semester of the 2022/2023 academic year. The data were collected by means of interviews, observations, and test. The data analysis techniques used were qualitative and quantitative. Based on the results of this research, it shows that the problem based learning model can improve students social skills and social learning outcomes in class IV of Kanisius Demangan Baru I Elementary School. Based on the results of data analysis, there was an increase social skills starting from the precycle stage to cycle 2, which initially the average social skills of students was 26% to 78%. The average social skills of students in one class increased 52%. Students learning outcomes also increased, based on preliminary data from pre-cycle to cycle 2. The average completeness of student learning outcomes in the pre-cycle stage was 26% to 78%. Average of social learning outcomes off class IV increased 48%.